Efficacy of Chinese Herbal Injections for Elderly Patients With pneumonia—A Bayesian Network Meta-analysis of Randomized Control Trials - Yuan, Yang; Zheng, Quan; Si, Zhilin; Liu, Juhua; Li, Zhi; Xiong, Lian; Liu, Pan; Li, Xu; He, Chengshi; Liang, Jinghong (Frontiers in Pharmacology, 2021)
Background: Pneumonia is a prevalent and complicated disease among adults, elderly people in particular, and the debate on the optimal Chinese herbal injections (CHIs) is ongoing. Our objective is to investigate the comparative effectiveness of various CHIs strategies for elderly patients with pneumonia. Methods: A comprehensive search strategy was executed to identify relevant randomized controlled trials (RCTs) by browsing through several databases from their inception to first, Feb 2020; All of the direct and indirect evidence included was rated by Network meta-analysis under a Bayesian framework. Results: We ultimately identified 34 eligible randomized controlled trials that involved 3,111 elderly participants and investigated 4 CHIs combined with Western medicine (WM) (Xiyanping injection [XYP]+WM, Yanhuning injection [YHN]+WM, Tanreqing injection [TRQ]+WM, Reduning injection [RDN]+WM), contributing 34 direct comparisons between CHIs. Seen from the outcome of Clinical effective rate and time for defervescence, patients taking medicine added with CHIs [Clinical effective rate, XYP + WM(Odd ratio (OR): 0.74, 95%Credible intervals (CrIs):0.55–0.98), YHN + WM(OR: 0.66, 95%CrI: 0.45–0.95), TRQ + WM(OR: 0.65, 95%CrI: 0.50–0.83), RDN + WM(OR: 0.60, 95%CrI: 0.40–0.89); Time for defervescence, YHN + WM(Mean difference (MD): −2.11, 95%CrI: −3.26 to −0.98), XYP + WM(MD: −2.06, 95%CrI: −3.08 to −1.09), RDN + WM(MD: −1.97, 95%CrI: −3.61 to −0.35), TRQ + WM(MD: −1.69, 95%CrI: −2.27 to −1.04)] showed statistically better effect compared with participants in the Control group (CG) who only took WM. Meanwhile, based on the time for disappearance of cough, 3 out of 4 CHIs [TRQ + WM(MD: −2.56, 95%CrI: −3.38 to −1.54), YHN + WM(MD: −2.36, 95%CrI: −3.86 to −1.00) and XYP + WM(MD: −2.21, 95%CrI: −3.72 to −1.10)] strategies indicated improvement of clinical symptoms. Only XYP + WM(MD −1.78, 95%CrI: −3.29 to −0.27) and TRQ + WM (MD: −1.71, 95%CrI: −2.71 to −0.73) could significantly shorten the time for disappearance of pulmonary rales. Conclusion: According to the statistical effect size (The surface under the cumulative ranking), we found that XYP + WM was presumably to be the preferable treatment for treating elderly patients with pneumonia compared with WM alone in terms of clinical effective rate. Our findings were based on very limited evidence and thus should be interpreted with caution. The application of the findings requires further research.